Enzyme-assisted extraction of polysaccharides from Dendrobium chrysotoxum and its functional properties and immunomodulatory activity. Issue 2 (March 2015) - Pan, Li-Hua; Wang, Jian; Ye, Xing-Qian; Zha, Xue-Qiang; Luo, Jian-Ping
Abstract: Dendrobium chrysotoxum has long been used as a health-promoting and therapeutic tonic in China. The polysaccharides from D. chrysotoxum (DCP) are considered to play an important role in its medical effects. The present study aimed at optimizing the technology for enzyme-assisted extraction (EAE) of DCP and at investigating the physicochemical characteristics and functional properties of DCP-E obtained by EAE and DCP-H obtained by hot water extraction (HWE). Based on single factor tests and orthogonal experiments of extraction pH, extraction temperature, cellulase amount and extraction time, the optimum conditions for CP-E were extraction pH value of 5.5, extraction temperature of 40 °C, cellulase amount of 10 g/L, extraction time of 3.0 h and solid/liquid ratio of 1:25. Under these conditions, the yield of DCP-E was 8.41 g/100 g dry weight, which was 1.25 times of that of DCP-H. As compared to DCP-H, DCP-E displayed an increased purity, a decreased molecular weight and relative viscosity as well as a changed monosaccharide compositions. Foam stabilization and splenic cell proliferation experiments showed that DCP-E had higher cell proliferation rate while DCP-H had better foam stabilization activity. These results indicate that different extraction methods would influence the physicochemical characteristics and subsequently functional properties of polysaccharides, suggesting that the suitable extraction method should be selected according to the application intention of polysaccharides. Highlights: Enzyme-assisted extraction conditions of DCP-E were optimized. DCP-E had a higher purity but a lower molecular weight and relative viscosity than DCP-H. DCP-E possessed higher cell proliferation rate than DCP-H. Compared with DCP-E, DCP-H showed better foam stabilization activity.